Comparative modelling and molecular docking of nitrate reductase from Bacillus weihenstephanensis (DS45). Issue 4 (1st October 2016) - Seenivasagan, R.; Kasimani, R.; Rajakumar, S.; Kalidoss, R.; Ayyasamy, P.M.
Abstract: Nitrate reductase catalyses the oxidation of NAD(P)H and the reduction of nitrate to nitrite. NR serves as a central point for the integration of metabolic pathways by governing the flux of reduced nitrogen through several regulatory mechanisms in plants, algae and fungi. Bacteria express nitrate reductases that convert nitrate to nitrite, but mammals lack these specific enzymes. The microbial nitrate reductase reduces toxic compounds to nontoxic compounds with the help of NAD(P)H. In the present study, our results revealed that Bacillus weihenstephanensis expresses a nitrate reductase enzyme, which was made to generate the 3D structure of the enzyme. Six different modelling servers, namely Phyre2, RaptorX, M4T Server, HHpred, SWISS MODEL and Mod Web, were used for comparative modelling of the structure. The model was validated with standard parameters (PROCHECK and Verify 3D). This study will be useful in the functional characterization of the nitrate reductase enzyme and its docking with nitrate molecules, as well as for use with autodocking.